TINJAUAN ELECTRONIC WORD OF MOUTH DAN PERSEPSI NILAI DALAM PENGARUHNYA TERHADAP MINAT KONSUMEN PADA PT. GO-JEK INDONESIA CABANG MAKASSAR - Ansir Launtu (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
This study aimed to analyze the influence of electronic word of mouth and the perception of value to the growing consumer interest in PT. Go-Jek Indonesia Makassar branch on South Sulawesi. This study is a survey research using questionnaires as instrument and taken as many as 70 respondents using purposive sampling method. The data collection is done by providing a list of questions to respondents who know or have ever used the services of Go-jack. This research use multiple linear regression analysis. The hypothesis was tested by t test and F test. The test results showed that the electronic word of mouth and the perception of value either partially or simultaneously positive and significant impact on consumer interest. Variables electronic word of mouth and is able to explain the variable value perception of consumer interest by 80.3% and the remaining 19.7% can be explained by other variables not included in the research model.